OPTIMASI CAKUPAN WIRELESS ACCESS POINT PADA MALL SUMARECON BEKASI - Rachmadini, Fernanda; Budhisantosa, Nugroho; Pramdhana, Dery Satya (Lembaga Penerbitan Universitas Esa Unggul, 2019)
AbstractThe performance of a Wi-Fi network in a mall can be seen from the signal received by users of the access point (AP). This research was conducted to analyze the performance of Wi-Fi network and optimize by taking the case in Mall Sumarecon Bekasi GF indoor floor by calculate the budget link to find the signal range of access points, coverage areas, Received Signal Strength Indicator (RSSI) using the Ekahau Site Survey application and checking connectivity using the Speedtest by Ookla. Optimization will be done by calculate the budget link with the RSL value obtained -61,5dBm, channel rearrangement and adding 3 access point according to number of access point needed to minimize interference and blank spot areas. The result of the optimization the budget link with the RSL value obtained -44,5dBm and the RSSI least then <-70dBm and the SNR least then <7dBm with stable connectivity in 5Mbps.Ã‚Â Keywords: Wi-Fi, Ekahau Site Survey, access point, budget link, RSSI, SNRÃ‚Â AbstrakKinerja jaringan Wi-Fi di Mall dapat dilihat dari sinyal yang diterima oleh pengguna access point (AP). Penelitian ini dilakukan untuk menganalisis kinerja jaringan Wi-Fi dan mengoptimalkan dengan mengambil kasus di Mall Sumarecon Bekasi pada lantai GF indoor dengan menghitung link budget untuk mengetahui jangkauan sinyal dari access point, area cakupan, Received Signal Strength Indicator (RSSI) menggunakan aplikasi ekahau site survey dan memeriksa konektivitas menggunakan Speedtest by Ookla. Optimasi akan dilakukan dengan menghitung link budget dengan nilai RSL yang didapatkan -61,5dBm, pengaturan ulang channel dan penambahan 3 access point sesuai dengan jumlah access point yang diperlukan untuk meminimalkan interferensi dan blank spot area. Hasil optimasi didapatkan link budget dengan nilai RSL menjadi -44,5dBm dan RSSI < -70dBm dan SNR > 7dBm dengan konektivitas stabil 5Mbps.Ã‚Â Kata kunci : Wi-Fi, Ekahau Site Survey, access point, link budget, RSSI, SNR